POPULATION STATUS OF FRANCOIS’ LANGUR (Trachypithecus francoisi) AT BA BE NATIONAL PARK - Thanh Hai, Dong (Journal of Forestry Science and Technology, 2016)
The Francois’ Langur (Trachypithecus francoisi) is an endangered primate belonging to subfamily Colobinae. The species was historically widespread in seven northern provinces of Viet Nam. Ba Be National Park is located in Vietnam’s northern mountains, and is a home to several small groups of T. francoisi. The objective of these surveys is to reveal distribution, group size and threats to species and its habitats. Results gathered will be use for making long term management and conservation of the species. Two Status Surveys were undertaken with a total of 21 field survey days between 13 - 26 February and 16 - 22 November 2009 at Ba Be National Park. Sighting of T. francoisi was rare in the surveyed areas, with only two groups of two and four individuals respectively detected in Pac Ngoi. Hunting and habitat destruction are main threats to the T. francoisi species and its habitat. Illegal logging poses a serious threat to the critical habitat of the leaf monkey, while shotguns and traps were identified as the main methods for hunting in the area. Immediate actions need to be conducted to conserve the remaining small populations of T. francoisi.